Sarcopenia is associated with 3-month and 1-year mortality in geriatric rehabilitation inpatients: RESORT. (12th July 2021) - Xu, Jane; Reijnierse, Esmee M; Pacifico, Jacob; Wan, Ching S; Maier, Andrea B
Abstract: Background: Sarcopenia is highly prevalent in geriatric rehabilitation patients and can worsen prognosis. This study aimed to investigate the association of sarcopenia and components of sarcopenia with 3-month and 1-year post-discharge mortality in geriatric rehabilitation inpatients. Methods: REStORing health of acutely unwell adulTs (RESORT) is an observational, prospective longitudinal cohort of geriatric rehabilitation inpatients. Sex-stratified Cox proportional-hazards analyses were used to associate sarcopenia (and its components) at admission, by the European Working Group on Sarcopenia in Older People (EWGSOP, EWGSOP2) and the Asian Working Group for Sarcopenia 2019 (AWGS 2019), with 3-month and 1-year post-discharge all-cause mortality. Results: Patients ( n  = 1, 406) had a median interquartile ranges [IQR] age of 83.0 [77.4–88.2] years (58% females). Sarcopenia was significantly associated with 3-month and 1-year mortality in females (EWGSOP, EWGSOP2 and AWGS 2019) and males (EWGSOP2, AWGS 2019). In females, low muscle mass (EWGSOP, EWGSOP2 and AWGS 2019) was significantly associated with 3-month and 1-year mortality; low muscle strength (EWGSOP, EWGSOP2 and AWGS 2019) was significantly associated with 1-year mortality. For males, low muscle mass (EWGSOP2, AWGS 2019) was significantly associated with 3-month and 1-year mortality; low muscle strength (EWGSOP2, AWGS 2019) was significantly associated with 3-month mortality. The association between physical performance with mortality was not analysed due to less than five events (death) in patients with normal physical performance. Conclusions: Sarcopenia, low muscle mass and low muscle strength at admission are associated with a significantly higher risk of mortality post-discharge from geriatric rehabilitation, highlighting the need to measure muscle mass and strength in clinical practice.